Dynamic bandwidth allocation algorithm for a mixed traffic network - Fry, T.A.; Haddad, A.H.; Lee, C.C. (2000 IEEE International Conference on Control Applications, 2000)
Considers a TDMA system designed for voice traffic, and analyzes the effects of adding data services with a specific bandwidth allocation protocol. This protocol stipulates priority for voice and movable traffic boundaries, and allocates slots at designated update interval times. A controlled Markovian analytical model is developed and used to derive relevant system performance characteristics for voice and data traffic. Additionally, the model is used to explore the optimization of system parameters to maximize data capacity subject to specified voice traffic characteristics.